Measuring service quality of IP data over UMTS network - Abu-Galala, Mahmoud M. Taher (2006)
Third Generation (3G) services are becoming more and more required by the users for high demanding for higher data rate transfer. In order to ensure that, in the end, the subscriber is served with a proper Quality of Service, certain measurements must be performed. However, the key to have a right evaluation of such services requires a proper definition of the performance indicators that is related to that service. In this project, we present the analysis and performance to data service application (HTTP) aiming to identify the performance of a real WCDMA (Wide Code Division Multiple Access)-mobile telecommunication networks based on live 3G network. We will provide the analysis of the results that are obtained during WCDMA field measurements and some of the statistical measurements that were recorded during the test as well. The network was tested and the data was collected by using QVOICE as a measurement tool. In addition, we will illustrate the impact of some mechanisms that may have effect on the service performance such as coverage. Finally, based on the evaluation results, we provide a set of recommendations that might help to improve the service and fulfill the user's requirements.